Damage detection in Aerospace structures using Chirped fiber Bragg grating. (2022) - Dinesh kumar, D.; Sridhar raj, S.; Sivananth, V.; Ramkumar, V.
Abstract: In the aviation industry, there is a need to detect even the smallest damage in order to avoid a fatal accident. Aerospace structures undergo various kinds of damages due to the impact force of objects during flight. In particular, the forward- facing components like a wing leading edge are subjected to impact forces caused by natural incidents like bird strikes. This work investigates the damage detection on the wing's leading edge when hit by a bird during flight. The damage detection method proposed in this work uses Chirped Fiber Bragg Grating (CFBG) as a sensing element, whose reflection spectrum is analyzed to verify the presence of damage. The already existing methods make use of the Fiber Bragg Grating (FBG) sensor which has lesser impact than the CFBG sensor. The aircraft wing has been designed in SOLIDWORKS and strain simulation is carried out using COMSOL software. The parameters such as stress, strain and wave length shift are obtained which can be used for damage detection in aircraft structures.